EFEKTIVITAS MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA TEKS HIKAYAT FASE E - Suci Septia Wulandari; Ria Satini; Indriani Nisja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low ability to read hikayat texts of students due to their lack of understanding in understanding the content of reading and classical Malay language contained in the hikayat texts. The objectives of this research are as follows. First, to describe the ability to read hikayat texts without using the Cooperative Integrated Reading and Composition (CIRC) model of class X students of SMA Negeri 1 Pantai Cermin. Second, to describe the ability to read hikayat texts using the Cooperative Integrated Reading and Composition (CIRC) model of class X students of SMA Negeri 1 Pantai Cermin. Third, to describe the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model on the ability to read hikayat texts phase E of SMA Negeri 1 Pantai Cermin. This type of research is quantitative research with experimental research methods. The design of this research is a posttest-only control design. The population of this research is students of class XE-6 (control class) totaling 34 students and XE-3 (experimental class) totaling 34 students. The sampling technique of this research is purposive sampling. The data in this research is in the form of objective test scores based on hikayat text indicators. The results of the study based on the results of the analysis of the research data conducted showed that there was a significant influence of the use of the Cooperative Integrated Reading and Composition (CIRC) model on the ability to read the story text of class X students of SMA Negeri 1 Pantai Cermin because thitung>t tabel (2.963>1.170), so H0 was rejected and H1 was accepted, meaning that there was an influence of the use of the Cooperative Integrated Reading and Composition (CIRC) model on the ability to read the story text of class X students of SMA Negeri 1 Pantai Cermin.